Social and emotional wellbeing, natural helpers, critical health literacy and translational research: connecting the dots for positive health outcomes. (December 2015) - Drew, Neil
Objective: The tripartite framework for principled practice was developed as part of the Wundargoodie Aboriginal Youth and Community Wellbeing Programme. The programme engages natural helpers to enhance critical health literacy. This paper examines the importance of translational research to enhancing critical health literacy for this group of de facto health workers using the work of the Australian Indigenous Health InfoNet as an example. Translational research provides workforce support for those who are time poor and overburdened. Connecting these concepts and natural helpers will make a positive difference to Aboriginal health outcomes. Conclusions: There is a need for the development of translational research products that enhance the critical health literacy of natural helpers. The tripartite framework for principled practice supports reflective and accountable practice in the intercultural space to build trust and confidence between Aboriginal and non-Aboriginal people to enhance the opportunity for authentic knowledge production and transfer.